An Analysis of Problem-Based Learning Activities in Improving Students' Critical Thinking Skills and Intrapersonal Intelligence - Nisa, Ghaida; Sarwi, Sarwi; Subali, Bambang (Journal of Primary Education, 2021)
Environmental-based learning is important for science learning in elementary school. It also refers to the concrete stage of students' thinking skills in elementary school. The use of problem-based learning model based on ethnoscience needs to be developed as a holistic learning process. This research sought to analyze the use of problem-based learning model on students' critical thinking skills and intrapersonal intelligence. This research employed mixed methods with a concurrent embedded research design. It took place in Babalan Elementary School and Kedungmutih Elementary School, located in Demak Regency. The research samples consisted of 96 fourth grade elementary school students. The data were collected through test, observation, and questionnaire techniques. The regression results revealed that there were significant differences in student activities using problem-based learning on their critical thinking skills. Based on the results of simple regression, it was found that (p = 0.00) < (∝ = 0.05); meaning that student activities in using problem-based learning affect critical thinking skills. The critical thinking skills affected students' intrapersonal intelligence, as shown by the results of the sig (2-tailed) regression test of 0.00 < 0.05; meaning that critical thinking skills affect intrapersonal intelligence.